Association of serum chromium levels with malnutrition in hemodialysis patients - Ching-Wei Hsu; Cheng-Hao Weng; Cheng-Chia Lee; Tzung-Hai Yen; Wen-Hung Huang (BMC Nephrology, 2019)
Abstract Background Chromium is an essential trace metal that reduces oxidative stress and inflammation. In patients undergoing maintenance hemodialysis (MHD), a correlation among chromium exposure, inflammation, and malnutrition remains unclear. This study examined the possible effects of serum chromium levels (SCLs) in MHD patients. Methods Initially, 732 MHD patients in dialysis centers were recruited. A total of 647 patients met the inclusion criteria and were stratified by SCL into four equal-sized groups: first quartile (< 0.29 μg/L), second quartile (0.29–0.56 μg/L), third quartile (0.57–1.06 μg/L), and fourth quartile (> 1.06 μg/L). Demographic, biochemical, and dialysis-related data were obtained for analyses. The analysis included nutritional and inflammatory markers. Results As compared with the highest quartile group, more subjects in the lowest quartile group were of an older age; had lower hemoglobin and creatinine levels; had a higher prevalence of DM and malnutrition (serum albumin level < 3.6 g/dL); and higher serum transferrin saturation and ferritin levels. A stepwise multiple linear regression analysis revealed a significant negative correlation between malnutrition and SCL (β coefficient = − 0.129, p = 0.012) and negative associations among body mass index (β coefficient = − 0.010, p = 0.041), ferritin (β coefficient = − 0.107, p = 0.001) and SCL. A multivariate logistic regression analysis also demonstrated a negative correlation between malnutrition and SCL. With a 10-fold increase in SCL, the risk ratio of malnutrition was 0.49 (95% confidence interval: 0.25–0.96; p = 0.039). Conclusions SCL is significantly associated with malnutrition in MHD patients. Further evaluation of the relationship between clinical outcomes (morbidity/mortality) and SCL is necessitated.